Changing communities, changing policing. - (:unkn) unknown (NWV Verl., 2018)
Based upon the research conducted over the course of the Citizen Interaction Technologies Yield Community Policing (CITYCoP) project, funded by the European Union's Horizon 2020 research and innovation programme, Changing Communities, Changing Policing focuses on four interrelated dimensions of community policing: law enforcement organizations (LEAs), citizens, technology and fundamental rights. First, the book offers a unique typology of organizational strategies to address participation dynamics within the community policing paradigm, in addition to a comparative perspective on the Anglo-American and the Continental-European models of community policing. Second, it examines the factors impacting the attitudes of citizens to the use of community policing apps. Third, it describes the generic approaches which information and communication technology (ICT) experts can utilize in the construction of community policing ICT systems, and recommends best practices for the use of social media analytics for community policing purposes. Finally, the book explains how fundamental rights, such as the right to the protection of personal data, can be observed at the stage of the design of community policing ICT systems, how best to benefit from different ICT-enhanced community policing methodologies without jeopardizing fundamental rights, and how digital solutions for community policing facilitate access by marginalized groups to law enforcement services.
Keywords: Öffentliche Sicherheit; Polizei; Gemeinde; Digitalisierung; Kommunikation; Soziale Medien; Bürger; Informationstechnologie; Internet; Governance; Menschenrecht; Privatsphäre; Kriminalitätsprävention; Bürgerwehr; Data Mining; Tracking; App